Skyrocket your business with social media branding : personalize, increase, and grow demand for your brand - Bradford, Isis (Ascent Audio, 2023)
Grow your business and your brand. Social media strategist and content expert Isis Bradford created this guidebook to help small business owners acclimate to social media branding and promoting digital products and goods. Learn how to utilize an Instagram following to your advantage without a business development manager using Bradford's The P.A.I.D. Equation method. P.A.I.D stands for how to (P)ersonalize the experience of your audience, bring (A)wareness to your business daily, create an (I)ntimate relationship with those who are ready to shop from you, and increase (D)emand for purchases! Social media and business strategies made simple. Engage with your audience using updated strategies on social media branding. Learn how to personalize intended experiences for your audience, build brand awareness daily on social media, and inspire your audience to purchase any of your digital products and courses without famous influencers. In this book, you'll find marketing and social media branding guidelines to grow your business, as well as business strategies to inspire purchases of your digital products and courses.